2010
DOI: 10.1007/s11010-010-0686-0
|View full text |Cite
|
Sign up to set email alerts
|

Salt modulates vascular response through adenosine A2A receptor in eNOS-null mice: role of CYP450 epoxygenase and soluble epoxide hydrolase

Abstract: High salt (HS) intake can change the arterial tone in mice, and the nitric oxide (NO) acts as a mediator to some of the receptors mediated vascular response. The main aim of this study was to explore the mechanism behind adenosine-induced vascular response in HS-fed eNOS+/+ and eNOS−/− mice The modulation of vascular response by HS was examined using aortas from mice (eNOS+/+ and eNOS−/−) fed 4% (HS) or 0.45% (NS) NaCl-diet through acetylcholine (ACh), NECA (adenosine-analog), CGS 21680 (A2A AR-agonist), MS-PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 44 publications
(72 reference statements)
9
57
0
Order By: Relevance
“…5), suggesting that sEH deletion enhances NECA-induced vascular relaxation. Our data show that NECA-induced vascular response in aortas of sEH Ϫ/Ϫ mice is similar to that from our earlier reports in which we found that high-salt diet-fed WT (C57BL/6J) mice had an enhanced NECA-induced relaxation with upregulation of A 2A AR, CYP2J-epoxygenase and downregulation of sEH, whereas, NECA-induced vascular response in aortas of sEH ϩ/ϩ mice is similar to that found in our earlier reports in which low-salt diet-fed WT (C57BL/6J) mice had an enhanced NECA-induced contraction with downregulation of A 2A AR, CYP2J-epoxygenase and upregulation of sEH (37,38). Therefore, in the present study, we used specific A 2A AR antagonists (ZM-241385 and SCH-58261) to rule out the involvement of other adenosine receptors (A 1 , A 2B , A 3 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…5), suggesting that sEH deletion enhances NECA-induced vascular relaxation. Our data show that NECA-induced vascular response in aortas of sEH Ϫ/Ϫ mice is similar to that from our earlier reports in which we found that high-salt diet-fed WT (C57BL/6J) mice had an enhanced NECA-induced relaxation with upregulation of A 2A AR, CYP2J-epoxygenase and downregulation of sEH, whereas, NECA-induced vascular response in aortas of sEH ϩ/ϩ mice is similar to that found in our earlier reports in which low-salt diet-fed WT (C57BL/6J) mice had an enhanced NECA-induced contraction with downregulation of A 2A AR, CYP2J-epoxygenase and upregulation of sEH (37,38). Therefore, in the present study, we used specific A 2A AR antagonists (ZM-241385 and SCH-58261) to rule out the involvement of other adenosine receptors (A 1 , A 2B , A 3 ).…”
Section: Discussionsupporting
confidence: 85%
“…Recently, we found that there is a possible link between the upregulation of A 2A AR, CYPepoxygenases, and downregulation of sEH with adenosineinduced relaxation in high-salt diet-fed WT mice (C57BL/6J) and eNOS Ϫ/Ϫ (C57BL/6J background) compared with low-salt diet-fed mice (38,39). Also, we found that there is a possible link between the downregulation of A 2A AR, CYP-epoxygenases and upregulation of sEH with NECA-induced contraction in low-salt diet-fed WT mice and eNOS Ϫ/Ϫ (C57BL/6J background) compared with high-salt diet-fed mice (38,39). The current study shows that in the absence of sEH, there is an increase in aortic A 2A AR, CYP2J5, PPAR␥, and a decrease in A 1 AR, PPAR␣ proteins compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulation of A2R is known to activate the endothelial and possibly also tubular cytochrome P450 (CYP450)-dependent metabolism of arachidonic acid [7,11,12,13,14,15]. Since the major active metabolites of the CYP450 pathway - epoxyeicosatrienoic acids (EETs) and 20-hydroxyeicosatetraenoic acid - are both vasoactive and transport inhibitory, they are likely to mediate the post-ADO changes in excretion.…”
Section: Introductionmentioning
confidence: 99%